Pragmatic Language in Children with Development Language Disorder : A Systematic Review - Sudrajad, Kiyat; Purnningrum, Windiarti Dwi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Developmental Language Disorder is an internationally recognized diagnostic term for people who have difficulty understanding and using language. Objectives: To analyze pragmatic abilities in children with Developmental Language Disorder and learning materials in writing scientific research while providing additional information about pragmatic abilities in children with Developmental Language Disorder. Methods: The research conducted is a systematic review study. This study uses data from previous studies. A quantitative systematic review combines findings from various independent studies, and produces a statistical summary of the findings (Last, 2001 in Murti, 2018). Results: Children with Developmental Language Disorder show a continuous language development condition with language problems. Where cognitive abilities are the main capital in communication. Conclusion: pragmatics is for talking, informing something and expressing feelings. Pragmatics is used to know what to say, how to say it and when is the right time to say a sentence. Keywords: Pragmatic Language, DLD, systematic review